2016
DOI: 10.1002/hbm.23311
|View full text |Cite
|
Sign up to set email alerts
|

Functional topography of the right inferior parietal lobule structured by anatomical connectivity profiles

Abstract: The nature of the relationship between structure and function is a fundamental question in neuroscience, especially at the macroscopic neuroimaging level. Although mounting studies have revealed that functional connectivity reflects structural connectivity, whether similar structural and functional connectivity patterns can reveal corresponding similarities in the structural and functional topography remains an open problem. In our current study, we used the right inferior parietal lobule (RIPL), which has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 88 publications
1
35
0
Order By: Relevance
“…Barbas and Rempel‐Clower, ; Fan et al, ; van den Heuvel et al, ]. However, the gross correspondence of the parcellation results based on different features or even sub‐features, for example, different immunohistochemical markers or different connection types in this study, still remains unclear, weaker‐ or even noncorresponding results exist in many studies [Fan et al, ; Liu et al, ; Moerel et al, ; Wang et al, ]. For example, both left and right inferior parietal lobule (LIPL/RIPL) were parcellated into seven regional cytoarchitectonic subregions [Caspers et al, ], but three receptor distributed subregions [Caspers et al, ] and five tractographically defined subregions [Mars et al, ; Wang et al, ].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Barbas and Rempel‐Clower, ; Fan et al, ; van den Heuvel et al, ]. However, the gross correspondence of the parcellation results based on different features or even sub‐features, for example, different immunohistochemical markers or different connection types in this study, still remains unclear, weaker‐ or even noncorresponding results exist in many studies [Fan et al, ; Liu et al, ; Moerel et al, ; Wang et al, ]. For example, both left and right inferior parietal lobule (LIPL/RIPL) were parcellated into seven regional cytoarchitectonic subregions [Caspers et al, ], but three receptor distributed subregions [Caspers et al, ] and five tractographically defined subregions [Mars et al, ; Wang et al, ].…”
Section: Discussionmentioning
confidence: 72%
“…To address these issues, three CBP schemes based on probabilistic diffusion tractography (PDT‐CBP) [Fan et al, ], resting‐state functional connectivity (rsFC‐CBP) [Wang et al, ], and meta‐analytic connectivity modeling (MACM‐CBP) [Ray et al, ] were used to parcellate the NAc. For the former two schemes, we used high‐quality MRI data from the Human Connectome Project (HCP) [Sotiropoulos et al, ; Van Essen et al, ] and applied mixed registration methods.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to connectivity, studies showed that single‐subject connectivity patterns from diffusion weighted imaging [Osher et al, ; Saygin et al, ] and resting‐state fMRI [Tavor et al, ] predict if an area is activated during task‐based fMRI on a voxel‐by‐voxel level; this finding that was replicated across several cognitive (task) domains. Connectivity‐based parcellations have been found recently not only within the TPJ [Bzdok et al, ; Mars et al, ], but also within several other areas of the social brain, such as the medial prefrontal cortex [Bzdok et al, ; Eickhoff et al, ; Neubert et al, ; Sallet et al, ], posterior medial cortex/precuneus [Bzdok et al, ; Margulies et al, ], and the inferior parietal lobule [Bzdok et al, ; Wang, et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported to be a critical region for spatial attention and play a vital role in fluent reading (Wei et al, ). Inferior frontal gyrus and precentral gyrus have been reported to be activated in various phonological and speech processing tasks (Cao et al, ; Price, ; Zhang, Shu, Zhou, Wang, & Li, ), with the former associated with phonological retrieval (Liu et al, ) and the latter associated with speech articulation (Fan, Mccandliss, Fossella, Flombaum, & Posner, ; Liu et al, ; Wang et al, ). Superior frontal gyrus is thought to be a part of cognitive execution network, involved in working memory and attention (Li et al, ).…”
Section: Discussionmentioning
confidence: 99%